Warcross - Lu, Marie, 1984- (London, UK : Penguin Books, 2017)
"When teenage coder Emika Chen hacks her way into the opening tournament of the Warcross Championships, she glitches herself into the game as well as a sinister plot with major consequences for the entire Warcross empire"--
First published in the United States of America by G.P. Putnam's Sons, an imprint of Penguin Random House, LLC, 2017.
Series from publisher's website
SHS
In English
Keywords: Internet games -- Fiction; Computer crimes -- Fiction; Hackers -- Fiction; Spies -- Fiction; Bounty hunters -- Fiction